Determinism and the possibility of morality - Dr. Zahoor H. Baber (Journal of Islamic Thought and Civilization, 2012)
The possibility of morality in a causally determined physical world engages philosophers in a serious debate. Many philosophers think that morality is not possible in a world where everything, including human actions, is determined by antecedent causal conditions. However, attempts to reconcile these apparently contradictory views have come forth. What emerges through the debate is that even if all human actions are causally determined, moral commitments are irreplaceable. Therefore, it is argued that causal determination of our thoughts and actions does not change the truth of morality. However, a morality involving determinism seems to rely heavily on the causal efficacy of moral judgments rather than the possibility of a free action. The deterministic morality focuses on human motivation as a cause and ignores the possibility of free choice. Moreover, a deterministic morality is unable to account for the freedom of the will. However, in serious climate of opinion, morality essentially involves moral responsibility based on a free choice and action. Thus, philosophical attempts to reconcile determinism and morality under the assumption of irreplaceable human interpersonal attitudes seem not so convincing. This paper brings forth the philosophical arguments involved; centralizing on the contention that morality cannot be subsumed under determinism.